2003
DOI: 10.1212/01.wnl.0000068333.43005.12
|View full text |Cite
|
Sign up to set email alerts
|

Dysferlin mutations in Japanese Miyoshi myopathy

Abstract: Four mutations (C1939G, G3370T, 3746delG, and 4870delT) are relatively more prevalent in this population, accounting for 60% of the mutations in this study. This study revealed that the G3370T mutation was associated with milder forms of MM and the G3510A mutation was associated with a more severe form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 23 publications
4
74
1
1
Order By: Relevance
“…All mutations in the DYSF gene found to date are point mutations or small deletions or insertions distributed all over the entire coding sequence. No hotspot has been identified, and missense as well as nonsense or frameshift mutations have been reported (Aoki et al, 2001;Takahashi et al, 2003). Consequently, mutation analysis of DYSF remains a time-consuming challenging task accounting for the paucity of large series.…”
Section: Doi: 101002/humu9355mentioning
confidence: 99%
“…All mutations in the DYSF gene found to date are point mutations or small deletions or insertions distributed all over the entire coding sequence. No hotspot has been identified, and missense as well as nonsense or frameshift mutations have been reported (Aoki et al, 2001;Takahashi et al, 2003). Consequently, mutation analysis of DYSF remains a time-consuming challenging task accounting for the paucity of large series.…”
Section: Doi: 101002/humu9355mentioning
confidence: 99%
“…Mutational data from large cohorts of patients repeatedly revealed a large mutational spectrum for the DYSF gene, with a high proportion of missense changes, or frameshifting insertions and/or deletions (for example, (Aoki, et al, 2001;Cagliani, et al, 2003;De Luna, et al, 2007;Guglieri, et al, 2008;Klinge, et al, 2010;Krahn, et al, 2009a;Mahjneh, et al, 1996;Nguyen, et al, 2005;Tagawa, et al, 2003;Takahashi, et al, 2003)). Accordingly, most of the UMD-DYSF entries correspond to "private" or rare DYSF disease-causing mutations.…”
Section: General Statisticsmentioning
confidence: 99%
“…Therefore, an easier method to screen for common mutations is now required to facilitate DNA-based diagnosis of dysferlinopathy. We previously showed that 4 mutations, c.937+1G>A, c.1566C>G, c.2997G>T and c.3373delG account for 50% of all the mutations identified in Japanese dysferlinopathy patients (4). In this study, we have developed a simple and rapid screening method to detect these mutational hot spots in the dysferlin gene using fluorescent primer extension.…”
Section: Introductionmentioning
confidence: 99%